Optimisation of the Motor Fleet Work in Road Haulage - Hrvoje Baričević (Promet (Zagreb), 2012)
The fleet of cars as one of the factors in the technologicalprocesses in transport has to be dimensioned in the optimalway. Market requirements are continually subject to changes,hence the demand for transportation services has to be modelledby means of quantitative methods. A mathematical modelfor determining the optimum size of the motor pool finds in thepaper its hypothetical presentation.